PENGARUH APLIKASI BACILLUS SP. 140-B DAN STREPTOMYCES SP. L.3.1-DW TERHADAP INFEKSI FUSARIUM OXYSPORUM SCHLECHT F. SP. CUBENSE (FOC) DAN PERTUMBUHAN TANAMAN PISANG (MUSA ACUMINATA) VAR. CAVENDISH - Laili, Nur; Antonius, Sarjiya; Salamah, Andi (Perhimpunan Biologi Indonesia, 2015)
Fusarium oxysporum Schlecht f. sp. cubense (Foc) is the causal pathogen of wilt disease of banana. Abilities of biocontrol agents Bacillus sp. 140-B and Streptomyces sp. L.3.1-DW to control Foc infection in banana were studied. Application of Bacillus sp. 140-B and Streptomyces sp. L.3.1-DW as single isolate or their combination in banana were tested under greenhouse conditions for 30 days. The aims of this study were to evaluate the potential of Bacillus sp. 140-B and Streptomyces sp. L.3.1-DW as biocontrol agents in banana. Treatments of biocontrol showed significant effect on the reduction of foc infection diseases of banana, compared to control. The lowest disease severity was found on the treatment of single isolate Streptomyces sp.L.3.1-DW with infection degree of 29,33%. Streptomyces sp. L.3.1-DW could suppress Foc population (6,25 x 105 CFU/ml) in rhizosphere area after 30 days innoculation. Bacillus sp. 140-B and Streptomyces sp. L.3.1-DW were also act as plant growth-promoting rhizobacteria (PGPR), that indicated by improvement of banana growth, in which Streptomyces L.3.1-DW caused the highest growth of banana either with or without Foc infection. This study indicated that Bacillus sp. 140-B and Streptomyces sp. L.3.1-DW have potential as alternative solutions to control Fusarium wilt in banana var. Cavendish. Keywords: Bacillus sp. 140-B, banana, biocontrol, Foc, PGPR, Streptomyces sp. L.3.1-DW.